Old-age poverty in the ASEAN member states: a scoping review of the literature - Haron, Sharifah Azizah; Foh, Foong Hui; Hamid, Tengku Aizan; Abdullah, Siti Farra Zillah; Tyng, Chai Sen (Human Resource Management Academic Research Society, 2022)
Poverty eradication remains a top priority for policymakers around the world. At the same time, population aging trends indicate a strong need to understand and address poverty in later life. While there is a lot of literature on poverty, there is not much on old-age poverty. The goal of this review is to outline current empirical research on old-age poverty, identify knowledge gaps, and make recommendations for future research. Comparison analysis had been done among ten countries in ASEAN members. The findings reveal most of the old age poverty is female. While health issues are the paramount factor that affected old-age poverty. Moreover, social pension schemes and financial assistance are crucial in eradicating old-age poverty. The results of this study have implications for understanding old-age poverty in ASEAN member countries from a profile of old-age poverty, factors that influence old-age poverty, and viable eradication policies and programs in developing countries worldwide.